2013
DOI: 10.5195/cajgh.2013.48
|View full text |Cite
|
Sign up to set email alerts
|

TB case detection in Tajikistan – analysis of existing obstacles

Abstract: BackgroundTajikistan National TB Control ProgramObjective(1) To identify the main obstacles to increasing TB Detection in Tajikistan. (2) To identify interventions that improve TB detection.MethodsReview of the available original research data, health normative base, health systems performance and national economic data, following WHO framework for detection of TB cases, which is based on three scenarios of why incident cases of TB may not be notified.ResultsData analysis revealed that some aspects of TB case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Although earlier a Knowledge, Attitude and Practice (KAP) survey conducted jointly by Project HOPE, WHO Tajikistan, and Sino Project/Swiss Center for International Health in 2005 and 2008 indicated room for improvement in raising public awareness of TB, the two surveys showed improved knowledge of TB symptoms among respondents over a 3-year period. 6 A qualitative study in 2006, consisting of 13 focus group discussions among 43 community members, echoed that overall knowledge of TB symptoms was accurate among community members. 11 Since then, the country has implemented various initiatives of patient support groups and community leaders training in expansive scales.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although earlier a Knowledge, Attitude and Practice (KAP) survey conducted jointly by Project HOPE, WHO Tajikistan, and Sino Project/Swiss Center for International Health in 2005 and 2008 indicated room for improvement in raising public awareness of TB, the two surveys showed improved knowledge of TB symptoms among respondents over a 3-year period. 6 A qualitative study in 2006, consisting of 13 focus group discussions among 43 community members, echoed that overall knowledge of TB symptoms was accurate among community members. 11 Since then, the country has implemented various initiatives of patient support groups and community leaders training in expansive scales.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Evaluations of EQA systems and/or blinded random re-checking strategies in TB microscopic laboratories had been conducted in various countries with high TB burden. 6 – 8 Our study performed the first evaluation on the EQA system and the performance of the TB microscopic laboratories in Sughd, Tajikistan since system implementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rao et al [15] reported that 16.7% of patients were not aware of TB and hence did not collect the report. Korobitsyn et al [16] reasoned that the suboptimal qualification of health centers and funding as well as improper management and supervision practices of TB patients were reasons for initial default.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for low TB case detection can be related to the healthcare system or patientrelated factors. Lack of f adequate training of health professionals on the diagnosis and treatment of TB a common healthcare system factor affecting TB case detection [11][12][13][14]. Different interventions were designed to enhance TB case detection in the national TB programs.…”
Section: Introductionmentioning
confidence: 99%